Provincial foreign direct investment absorptive capacity of Vietnam - Duong Hoang Vu; Tri Thanh Ho (Entrepreneurial Business and Economics Review (EBER), 2020)
Objective: The objective of the article is to examine the importance of absorptive capacity in the relationship between foreign direct investment and economic performance in 63 Vietnamese provinces from 2007 to 2015. Research Design & Methods: The absorptive capacity at provincial level includes six components tested by confirmatory factor analysis, which allows for the argument that absorptive capacity of domestic firms is an important component of absorptive capacity of provinces. Besides this one, there are five other components, including financial development, human capital, the level of openness, the absorptive capacity of domestic firms, institutions, and infrastructure. The generalized two-stages least squares (G2SLS) random effect with instrumental variables regression is used with panel data. Findings: Firstly, foreign direct investment has a positive impact on the development of the 63 provinces in Vietnam. Secondly, among the six components, the four most important ones are infrastructure, the level of openness, human capital, and the absorptive capacity of domestic firms. Moreover, the article finds that foreign direct investment can bring negative impacts to provinces with a low level of trade openness. Implications & Recommendations: The government should focus on infrastructure, trading policy, human capital and capability of domestic firms. Contribution & Value Added: There is a lack of connection between absorptive capacity at the firm level and the macro level. Therefore, this article attempts to create this connection by constructing absorptive capacity at the firm level as a component of absorptive capacity at the provincial level.
Keywords: F14; F23; F62; 330; Absorptive capacity; Openness; Financial development; The absorptive capacity of domestic firms